The morphometric, meristic and genetic characteristics of European sprat (Sprattus sprattus) in the Black Sea - Salih İlhan; Zehra Duygu Düzgüneş; Nazlı Kasapoğlu (Journal of Fisheries, 2023)
The European sprat (Sprattus sprattus) represents the unit stock shared among the Black Sea countries. It has a key role in the Black Sea ecosystem and is determined by its importance from both a commercial and an ecological point of view. Up to now, there are few studies on the meristic, morphometric and genetic characteristics of this species. In this study, the species were specified and studied for meristic, morphometric and genetic characteristics. Mitochondrial gene regions which 16S rRNA and cytochrome c oxidase subunit I (COI), were studied and compared with some of the family Clupeidae species in the National Center for Biotechnology Information (NCBI) and the phylogenetic relationship was examined. A total of 14 haplotypes were determined for the mitochondrial COI gene region and 3 haplotypes were determined for the 16S rRNA gene region. This study will contribute to the sustainable management of this species as well as be a basis for future studies.